OPTIMALISASI INSTAGRAM @alfamidigemabudaya_bekasi SEBAGAI MEDIA INFORMASI BUDAYA KERJA ALFAMIDI BRANCH BEKASI - Brenda Syahirah; Amiruddin Saleh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
With the development of technology in today's digital era, social media has become a very effective means of conveying information quickly, widely, and interactively. Alfamidi, as part of a modern retail network, not only focuses on product sales but also strives to build a positive and professional work culture among its employees. This study aims to analyze the optimization of the Instagram account @alfamidigemabudaya_bekasi and identify the challenges faced in the content production process. This internship at PT. Midi Utama Indonesia Tbk aims to analyze the Instagram content management strategy implemented by social media specialists in introducing the work culture of Alfamidi Bekasi Branch employees and to analyze the tasks of social media specialists in increasing engagement through Instagram @alfamidigemabudaya_bekasi using the Uses and Gratifications (U&G) theory. The research method employed a qualitative approach through observation, active participation, interviews, and literature review during the four-month internship. The research results indicate that the communication strategy of @alfamidigemabudaya_bekasi has been effective in strengthening internal branding and fostering a sense of camaraderie among employees. However, optimization is still needed in technical aspects to make social media management more effective, professional, and impactful. Nevertheless, there are still several challenges in its implementation. The results of the study show that the communication strategy of @alfamidigemabudaya_bekasi has been effective in strengthening internal branding and building a spirit of togetherness among employees, although optimization is still needed in technical aspects so that social media management becomes more effective, professional, and has a wider impact. However, in its implementation, there are still several challenges that hinder daily content production and reduce the effectiveness of content production on Instagram @alfamidigemabudaya_bekasi. These include limited human resources and a lack of content production facilities such as cameras, lighting, and editing equipment, which are needed to produce more professional and time-efficient content, as well as the lack of social media talent skills among store employees and their workload, which overlaps with their other main tasks.